2019
DOI: 10.1590/interface.170562
|View full text |Cite
|
Sign up to set email alerts
|

“Corpo de homem com (tre)jeitos de mulher?”: imagem da travesti por enfermeiras

Abstract: Trata-se de uma pesquisa qualitativa, fundamentada na Teoria das Representações Sociais, com o objetivo de descrever a imagem da pessoa travesti revelada por enfermeira(o)s. Aplicou-se Teste de Associação Livre de Palavras (TALP), composto pelo estímulo ‘Travesti’, para 110 enfermeira(o)s pós-graduanda(o)s de universidade pública do município de Salvador, Bahia, Brasil. Dessas, vinte responderam a entrevista semiestruturada. Os dados do TALP processados pelo software Ensemble de Programmes Permettant l’Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…Thus, it is possible to notice that the representation of nurses refers to a context of their practices evidenced in the term "prejudice". This corroborates the fact that there is difficulty in accepting differences, and both health professionals and society still reinforce and potentiate attitudes that generate suffering, exclusion, barriers and social distancing (3)(4)18) . However, tensions were observed in the relationship between the terms present in the CN and the peripheral ones, such as "bravery", "right" and "respect", which reverberate as transvestite people, possibly, are welcomed in the various spaces of the health care network.…”
Section: Believe That the Transvestite People's Image Is Very Linkesupporting
confidence: 68%
See 3 more Smart Citations
“…Thus, it is possible to notice that the representation of nurses refers to a context of their practices evidenced in the term "prejudice". This corroborates the fact that there is difficulty in accepting differences, and both health professionals and society still reinforce and potentiate attitudes that generate suffering, exclusion, barriers and social distancing (3)(4)18) . However, tensions were observed in the relationship between the terms present in the CN and the peripheral ones, such as "bravery", "right" and "respect", which reverberate as transvestite people, possibly, are welcomed in the various spaces of the health care network.…”
Section: Believe That the Transvestite People's Image Is Very Linkesupporting
confidence: 68%
“…This population has occupied a marginalized position in contemporary western societies (2) , which demands a singular view, including nursing, to meet their care demands. However, a survey conducted with nurses revealed that, among the investigated group, there is an image of transvestites as men, of homosexual sexual orientation, who use props to live an identity based on/by the female (3) .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nesse sentido, as travestis são consideradas transgressoras de uma "norma social" que ainda naturaliza e privilegia uma linha congruente entre genitália-gênero-desejos e práticas sexuais como modelo de humanidade e moralidade, o que é denominado de (cis)heteronormatividade, sendo alvo de preconceitos, estigmas discriminação e exclusão. Esses aspectos, sobremaneira, potencializam as vulnerabilidades para agravos sociais e de saúde que podem repercutir na qualidade de vida (6)(7) . Haja vista que, mesmo nos serviços especializados, considerados como os mais qualificados para o atendimento a esse segmento populacional, não é incomum a ocorrência de situações de discriminação vivenciadas por travestis quando acessam esses serviços (8)(9) .…”
Section: Segundo Dados Da Pesquisa "Diversidadeunclassified